Keabsahan Alat Bukti Chatting Melalui Media Sosial Dalam Proses Pemidanaan Terhadap Tindak Pidana Perzinahan - Ni Kadek Sri Wijayanti; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2025)
The rapid advancement of technology does not only bring positive impacts to society but also brings negative impacts such as infidelity through social media. Chat evidence is one of the important factors in uncovering adultery crimes. The position of chat evidence in criminal procedure law is still unclear. The formulation of the problems raised is 1) what is the validity of chat evidence through social media in the examination of the crime of adultery? and 2) what is the strength of the evidence of chat through social media in the criminal process of adultery? The research method uses normative legal methods by analyzing literature materials and focusing on laws and regulations. The results of the discussion show that the validity of chat evidence in the examination of adultery crimes must meet formal and material requirements, with the important role of digital forensic experts. The stages of evidence management involve identification, collection, confiscation, examination and reporting. The authenticity and relevance of forensic results is the main key, with reports and certification of forensic digital experts as the basis for proof in court. Chats can now be used as electronic evidence thanks to Law Number 11 of 2008 concerning Information and Electronic Transactions. They no longer only have evidentiary power, but also letter evidence and clues.